The Role Of Torsional Alfvén Waves in Coronal Heating - Antolin, P; Shibata, K (The Astrophysical journal, 2010)
In the context of coronal heating, among the zoo of magnetohydrodynamic (MHD) waves that exist in the solar atmosphere, Alfven waves receive special attention. Indeed, these waves constitute an attractive heating agent due to their ability to carry over the many different layers of the solar atmosphere sufficient energy to heat and maintain a corona. However, due to their incompressible nature these waves need a mechanism such as mode conversion (leading to shock heating), phase mixing, resonant absorption, or turbulent cascade in order to heat the plasma. Furthermore, their incompressibility makes their detection in the solar atmosphere very difficult. New observations with polarimetric, spectroscopic, and imaging instruments such as those on board the Japanese satellite Hinode, or the Crisp spectropolarimeter of the Swedish Solar Telescope or the Coronal Multi-channel Polarimeter, are bringing strong evidence for the existence of energetic Alfven waves in the solar corona. In order to assess the role of Alfven waves in coronal heating, in this work we model a magnetic flux tube being subject to Alfven wave heating through the mode conversion mechanism. Using a 1.5 dimensional MHD code, we carry out a parameter survey varying the magnetic flux tube geometry (length and expansion), the photospheric magnetic field, the photospheric velocity amplitudes, and the nature of the waves (monochromatic or white-noise spectrum). The regimes under which Alfven wave heating produces hot and stable coronae are found to be rather narrow. Independently of the photospheric wave amplitude and magnetic field, a corona can be produced and maintained only for long (>80 Mm) and thick (area ratio between the photosphere and corona >500) loops. Above a critical value of the photospheric velocity amplitude (generally a few km ssup -1) the corona can no longer be maintained over extended periods of time and collapses due to the large momentum of the waves. These results establish several constraints on Alfven wave heating as a coronal heating mechanism, especially for active region loops.